Fine-Resolution Spaceborne Radar Imaging of Space Targets With Parametric Second-Order Scaling and High-Order Spatial-Variant Phase Compensation - He Li; Rui Cao; Tianyuan Yang; Pingping Lu; Yijiang Nan; Robert Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
Spaceborne radar imaging is the key means to obtain the fine-resolution radar image of space targets. However, the nonuniform relative rotational motion caused by the high-speed orbital state leads to the degradation of the radar imaging performance. To address this problem, a fine-resolution spaceborne radar imaging method of space targets with parametric second-order scaling (PSOS) and high-order spatial-variant phase compensation is proposed in this article. First, an accurate echo signal model that has higher precision than the existing methods is derived, which considers the spatial-variant second-order migration through range cell (MTRC) and high-order phase error (SVPE). Then, the problem of the relative rotational motion parameters estimation is transformed as the optimization solution in the Doppler domain, and an efficient rotational motion estimation method with the time–frequency ridge extraction and Levenberg–Marquardt (L–M) algorithm is proposed. On this basis, a PSOS operation is proposed to correct the spatial-variant second-order MTRC. Afterward, a parametric high-order SVPE compensation function is introduced to achieve the azimuth focus. Finally, a fine-resolution spaceborne radar image of the space target can be obtained. The results of the simulated and measured data verify the advantages of the proposed method.